2016
DOI: 10.1021/jacs.6b08264
|View full text |Cite
|
Sign up to set email alerts
|

Digenite Nanosheets Synthesized by Thermolysis of Layered Copper-Alkanethiolate Frameworks

Abstract: Copper sulfide nanocrystals support localized surface plasmon resonances in the near-infrared wavelengths and have significant potential as active plasmonic nanomaterials due to the tunability of this optical response. While numerous strategies exist for synthesizing copper sulfide nanocrystals, few methods result in nanocrystals with both controlled morphological shapes and crystallinity. Here, we synthesize and characterize ultrathin (<5 nm) CuS nanosheets that are formed by solventless thermolysis, utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…The strong and broad NIR absorption bands observed in the spectra of the product CIS/ZnS HNCs obtained by using injection methods II and III ( Figure S3 ) are assigned to localized surface plasmon resonances (LSPR), which are often observed in Cu-chalcogenide NCs. 9 , 24 , 25 LSPR bands involve excess charge carriers, which are due to stoichiometry deviations, typically Cu-vacancies, which lead to excess holes in the valence band. 9 , 24 However, LSPRs due to In-vacancies have also been reported.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong and broad NIR absorption bands observed in the spectra of the product CIS/ZnS HNCs obtained by using injection methods II and III ( Figure S3 ) are assigned to localized surface plasmon resonances (LSPR), which are often observed in Cu-chalcogenide NCs. 9 , 24 , 25 LSPR bands involve excess charge carriers, which are due to stoichiometry deviations, typically Cu-vacancies, which lead to excess holes in the valence band. 9 , 24 However, LSPRs due to In-vacancies have also been reported.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 9 , 24 , 25 LSPR bands involve excess charge carriers, which are due to stoichiometry deviations, typically Cu-vacancies, which lead to excess holes in the valence band. 9 , 24 However, LSPRs due to In-vacancies have also been reported. 25 These observations imply that methods II and III lead to product HNCs that are rich in cation (Cu or In) vacancies, in contrast to method IV.…”
Section: Results and Discussionmentioning
confidence: 99%
“…NIR absorption bands similar to those displayed in the spectra of the template Cu 2– x Se NCs ( Figure 3 ) are commonly observed for Cu-chalcogenide NCs and have been ascribed to localized surface plasmon resonances due to excess charge carriers (typically valence band holes originating from Cu vacancies). 1 , 2 , 35 The NIR absorption bands are no longer present in the absorption spectra of the product NCs obtained from the CE reactions, indicating the absence of Cu vacancies and the successful conversion of the template Cu 2– x Se NCs into either CdSe or CuInSe 2 NCs, through Cu + for Cd 2+ or partial, self-limited Cu + for In 3+ CE, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Later (2016), Bryks et al demonstrated a similar Cl-assisted synthetic strategy for ultrathin Cu 9 S 5 nanosheets. 308 …”
Section: Semiconductor Nanocrystalsmentioning
confidence: 99%